Phenotypic divergence in two sibling species of shorebird: Common Snipe and Wilson's Snipe (Charadriiformes: Scolopacidae). (9th November 2020) - Rodrigues, Tiago M.; Miller, Edward H.; Drovetski, Sergei V.; Zink, Robert M.; Fjeldså, Jon; Gonçalves, David
Abstract : Natural and social selection are among the main shapers of biological diversity but their relative importance in divergence remains understudied. Additionally, although neutral evolutionary processes may promote phenotypic divergence, their potential contribution in speciation is often overlooked in studies of comparative morphology. In this study, we investigated phenotypic differentiation in two allopatric shorebirds: the Palaearctic Common Snipe Gallinago gallinago and the Nearctic Wilson's Snipe Gallinago delicata . Specimens of Common Snipe ( n  = 355 skins, n  = 163 skeletons) and Wilson's Snipe ( n  = 403 skins, n  = 141 skeletons) in natural history collections were examined to quantify differences in skeletal and external measurements, and measures of wing and tail plumage variables. The species do not differ in skeletal variables except for the relatively larger sternum of the Common Snipe. The two species do not differ in multivariate wing size or shape (pointedness). Previously known plumage differences between these species were confirmed: the Common Snipe has fewer rectrices, longer and wider outermost rectrices, more extensive white on tips of the secondary feathers, and more white in the axillaries. Between‐species variance in skeleton, primary length and plumage variables was greater than expected if drift was mainly responsible for phenotypic divergence, suggesting a role of selective processes. However, drift could not be rejected after adjusting for multiple comparisons. Differences in plumage traits were greater than in skeletal or external measurements. Because snipe use plumage traits in signalling, the results suggest a more rapid divergence in socially selected traits between these species than in traits related to resource use.